Greeny Quiche Bites, Alternatif Snack dengan Sirih Bumi (Peperomia Pellucida) Bagi Remaja - Annisa Rizkiriani; Nuraeni, Ani; Annisa Nurhidayati, Vieta; Mutiara Ramadanti, Lisya; Nurmahmudi, Muhammad; Intan Permatasari , Siti; Martini, Rina; Muhammad Basar, Firman (PUSAT SAINS INDONESIA, 2023)
Greeny Quiche Bites is a snack filled with daun sirih bumi as an alternative snack for adolescents. The aim of this research is to make Greeny Quiche Bites as an alternative snack with sufficient nutritional content for Adolescents. The results of this study show that each serving of 2 Greeny Quiche Bites, weighing approximately 100 g, contains 238 Cal of energy, 11.4 g of protein, 31.9 g of carbohydrates, 2.3 g of fiber, and 6.4 mg of iron. Greeny Quiche Bites contribute an average of 11,1% of the energy needs of adolescents aged 10-18 years. The overall category hedonic test results show that the panelists really like Greeny Quiche Bites. Based on the nutritional content, Greeny Quiche Bites can be used as an alternative snack with sufficient nutritional content and iron-rich for teenagers.